Superiority of radiotelemetry over the tail-cuff method in evaluating control and drug-induced data in cardiovascular functions - Lemmer, Björn (Biological rhythm research, 2016)
The aim of the study was to compare an often-used method to measure blood pressure (BP) using a tail-cuff (TC) device, with radiotelemetry (RT) which allows to sample data on heart rate (HR) and BP in freely moving rodents without any restraint in behaviour. Data were collected in male normotensive Wistar-Kyoto rats and in spontaneously hypertensive rats. Experiments were performed under 12:12 h light-dark conditions (lights on at 07:00 h) with simulated dawn and dusk for 45 min. Experiments were performed at 08:00-10:00 h (rest phase) and at 20:00-22:00 h (activity phase) under control conditions and after treatment with the beta-adrenoceptor blocker metoprolol (8 mg/kg). For TC, the Harvard BP Monitoring System (Edenbrigde, England) and for RT radio transmitters (Dataquest IV system, TA11PA-C40, DSI, St. Paul, Minnesota, USA) were used. Rats bearing the TC device were also monitored under RT. The experiments show that TC significantly increased HR and both systolic and diastolic BP in both strains and both at L and D. Metoprolol reduced TC-induced HR but left BP increase uneffected. The study shows that RT is the method of choice to monitor BP and HR in rodents, TC is not suitable.
Gesehen am 12.02.2019